RS13290979 POLYMORPHISM WITHIN NOTCH1 GENE IS ASSOCIATED WITH SEVERE BIOPROSTHETIC MITRAL VALVE CALCIFICATION - ANASTASIA V. Ponasenko; ANTON G. Kutikhin; MARIA V. Khutornaya; NATALIA V. Rutkovskaya; ANNA V. Tsepokina; NATALIA V. Kondyukova; ARSENIY E. Yuzhalin; LEONID S. Barbarash (Фундаментальная и клиническая медицина, 2018)
Aim. Bioprosthetic mitral valves frequently undergo severe calcification causing bioprosthetic valve failure, an urgent problem in cardiovascular surgery. However, no research have been performed on genetic susceptibility to severe bioprosthetic mitral valve calcification. Here we assessed whether inherited variation in genes of calcium metabolism is associated with severe bioprosthetic mitral valve calcification. Materials and Methods. We recruited 124 consecutive patients who underwent mitral valve replacement surgery. We assessed eight polymorphisms within the five genes: rs13290979 (NOTCH1 gene), rs731236 and rs2228570 (VDR gene), rs1042636 (CASR gene), rs3134069, rs2073618, rs3102735 (OPG gene) and rs1801197 (CALCR gene). Genotyping was carried out in 96-well format using the TaqMan SNP genotyping assay. Statistical analysis was performed utilizing the SNPStats software, with the calculation of the odds ratio according to codominant, dominant, recessive, overdominant, and log-additive models of inheritance. Adjustment for multiple comparisons was conducted using false discovery rate.Results. G/G genotype of the rs13290979 polymorphism within the NOTCH1 gene was associated with 2.75-fold increased risk of severe bioprosthetic mitral valve calcification compared to the A/A and A/G genotypes. Other genotypes did not show a significant association with this condition.Conclusions. Polymorphisms within the calcium metabolism genes (e.g., NOTCH1 gene) may be associated with severe bioprosthetic mitral valve calcification.